Engineering problems in developing and managing show caves - Cigna, Arrigo; Cucchi, Franco; Forti, Paolo (Journal of Nepal Geological Society, 2000)
Show caves play an important role in the socio-economic development of a country. A fast increase of such caves can be attributed to the increasing demand from tourists eager to observe natural features and phenomena. On the other hand, the karst environment is quite vulnerable to changes, and hence the transformation of a natural cave into a show cave must be designed, implemented, and managed with due attention to the problem of environmental protection. For this reason, the contribution of the engineering geology is instrumental. Engineering geology is particularly useful for the following activities. Environmental Impact Assessment including choice of the materials to minimise the environmental impact and to optimise the safeguard of tourists and employees; Identification and implementation of countermeasures for unstable zones in the cave; Design and construction of tourist pathways and other structures; Identification of the best light sources and their operation; Cave cleaning and maintenance (devices to supply water and to take out sewage, measures to minimise dust, and the problem of maintenance of old show caves); and Management of the surface area (planning and managing human activities in the outside area corresponding to the whole intake site for the karst system, as most of them may greatly affect the show cave environment, but, on the other hand, some of them such as parking, ticket office, and toilets are absolutely unavoidable). In the paper, the main engineering problems related to establishing and managing a show cave are presented together with practical examples from some of the main show caves in Italy and abroad.